Rohinton Mistry’s Diaspora - Manisha (International Journal of Multidisciplinary Research and Studies, 2021)
The study of the literature and other cultural works that pertain to the Indian diaspora is the primary focus of the book "Literature of the Indian Diasporic." In addition to that, it is a significant contribution to the field of diaspora theory in general. This anthology applies a theoretical framework based on trauma, mourning impossible, spectres, identity, travel, translation, and recognition, and uses the term "migrant identity" to refer to any ethnic enclave within a nation-state that defines itself, consciously or unconsciously, as a group that is in displacement.